BIG BOOK AS A MEDIA TO TEACH READING COMPREHENSION TO ELEMENTARY SCHOOL STUDENTS - Nofita Yola; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2017)
Learning in Primary Schools should be interesting and fun. It is intended that the students have the motivation when learning, so that students are not easily saturated in learning, especially learning reading comprehension. One way to make learning more fun and not monotonous is by using a media. Media can help the teachers in presenting the material, so that students more easily to understand that material. The great media that can be used the teacher in teaching reading comprehension is by using Big Book. Big Book shaped a great book, it contains a brief story with great writing and the colourful of pictures. This book can be used for elementary school children grades 4, 5 and 6. The author hopes of using this Big Book by the teachers to be more creative in the use of media and improving the quality of student learning, especially the ability to understand the text or story.